2005
DOI: 10.1191/0969733005ne809oa
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Moral Distress and Ethical Work Environment

Abstract: This study examined the relationship between moral distress intensity, moral distress frequency and the ethical work environment, and explored the relationship of demographic characteristics to moral distress intensity and frequency. A group of 106 nurses from two large medical centers reported moderate levels of moral distress intensity, low levels of moral distress frequency, and a moderately positive ethical work environment. Moral distress intensity and ethical work environment were correlated with moral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
587
5
19

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(643 citation statements)
references
References 35 publications
32
587
5
19
Order By: Relevance
“…The results of this study showed that ethical climate with average score of 3.48 with a standard deviation of 0.61 was moderate, in Corley et al (2005), this average was 3.33 out of 5 (6), in Ulrich et al Equal was 2.6 (7) that is less than the average of this study. Perhaps the reason for this difference in working conditions and organizational culture in Iran hospitals with other countries.…”
Section: Discussionmentioning
confidence: 39%
“…The results of this study showed that ethical climate with average score of 3.48 with a standard deviation of 0.61 was moderate, in Corley et al (2005), this average was 3.33 out of 5 (6), in Ulrich et al Equal was 2.6 (7) that is less than the average of this study. Perhaps the reason for this difference in working conditions and organizational culture in Iran hospitals with other countries.…”
Section: Discussionmentioning
confidence: 39%
“…In other fields also, the frequency with which health-care workers and trainees experience ethical confrontations are unclear. 16,18 Medical and nursing training and practice are often difficult, residents or nurses may also participate in procedures or resuscitations about which they have major reservations in other domains of practice. For example, ethical confrontations may be experienced by residents and nurses in the setting of performing liver transplantation in alcoholic patients, bariatric surgery, aesthetic surgery, prolonged and aggressive therapy after multiple relapses in oncology patients, intensive resuscitation of elderly patients with poor functioning, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical setting/population Gutierrez (2005), Meltzer and Huckabay (2004), Sundin-Huard and Fahy (1999) Critical care Aiken et al (2002), Corley et al (2005), Rice et al (2008) Medical/surgical care…”
Section: Author(s)mentioning
confidence: 99%